HPB PLENARY: OR-HPB-02: Endoscopic ultrasonography-guided intrahepatic portal vein embolization in an animal model - Park, Tae Young (Endosc Ultrasound, 2017)
BACKGROUND AND OBJECTIVES: Preoperative portal vein embolization (PVE) by percutaneous transhepatic approach has been performed in candidates of major liver resection including right hepatectomy and extended right hepatectomy. This procedure can increase volume of remnant liver and prevent postoperative hepatic failure. The aim of this animal study is to evaluate the technical feasibility and safety of endoscopic ultrasonography (EUS)-guided intrahepatic PVE. METHODS: EUS-guided intrahepatic PVE with coil and histoacryl was performed in seven pigs under general anesthesia using linear array echoendoscope. The intrahepatic portal vein (PV) was punctured with a 19-gauge FNA needle, and an embolization coil was inserted into the selected intrahepatic PV. Then, histoacryl was injected through the same FNA needle. The blood flow change in the selected intrahepatic PV was evaluated by color Doppler EUS. After 1-week observation period, necropsy was performed. RESULTS: Embolization coil was placed in the selected intrahepatic PV successfully in six of seven animals, and Histoacryl injection was successful in five of them. In one case, histoacryl injection was failed due to needle deflection and early clogging. After coil insertion and histoacryl injection, disappearance of blood flow in the treated intrahepatic PV was confirmed by color Doppler. There was no adverse event in six animals during 1-week observation period. Necropsy revealed no evidence of damage to the treated intrahepatic PV and intra-abdominal organs. CONCLUSIONS: EUS-guided intrahepatic PVE can be both technically feasible and safe in a live porcine model. Further animal studies are needed to demonstrate the efficacy and long-term safety of this challenging intervention.